2020
DOI: 10.1096/fj.202001016rr
|View full text |Cite
|
Sign up to set email alerts
|

PAN‐selective inhibition of cAMP‐phosphodiesterase 4 (PDE4) induces gastroparesis in mice

Abstract: Inhibitors of cAMP‐phosphodiesterase 4 (PDE4) exert a number of promising therapeutic benefits, but adverse effects, in particular emesis and nausea, have curbed their clinical utility. Here, we show that PAN‐selective inhibition of PDE4, but not inhibition of PDE3, causes a time‐ and dose‐dependent accumulation of chow in the stomachs of mice fed ad libitum without changing the animals' food intake or the weight of their intestines, suggesting that PDE4 inhibition impairs gastric emptying. Indeed, PDE4 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 112 publications
4
30
0
Order By: Relevance
“…Indeed, a prior study has shown that inhibition of PDE4 promoted the release of amylase from parotid acinar cells in culture 33 , which is consistent with the notion that βadrenoceptor-and cAMP-dependent saliva secretions are rich in protein 1,2 . Conversely, we propose that in awake mice, PDE4 inhibition may induce salivation via additional, central/neuronal regulations, in line with the high expression of PDE4 in brain 34 and the fact that PDE4 inhibition has been shown to affect other autonomic nervous system regulations including control of body temperature or gastrointestinal motility 17,20 . In an intriguing parallel, although the most widely used drug to induce salivation, Pilocarpine, can induce salivation by acting directly on the salivary glands (see Fig.…”
Section: Distinguishing Central and Direct Effects Of Pde4 Inhibition On Salivationmentioning
confidence: 84%
See 3 more Smart Citations
“…Indeed, a prior study has shown that inhibition of PDE4 promoted the release of amylase from parotid acinar cells in culture 33 , which is consistent with the notion that βadrenoceptor-and cAMP-dependent saliva secretions are rich in protein 1,2 . Conversely, we propose that in awake mice, PDE4 inhibition may induce salivation via additional, central/neuronal regulations, in line with the high expression of PDE4 in brain 34 and the fact that PDE4 inhibition has been shown to affect other autonomic nervous system regulations including control of body temperature or gastrointestinal motility 17,20 . In an intriguing parallel, although the most widely used drug to induce salivation, Pilocarpine, can induce salivation by acting directly on the salivary glands (see Fig.…”
Section: Distinguishing Central and Direct Effects Of Pde4 Inhibition On Salivationmentioning
confidence: 84%
“…PDE inhibitors were generally administered at a dose of 1 mg/kg (i.p. ), which has been shown to produce ≥50% of maximal efficacy on a variety of acute phenotypes of PDE4 inhibition in mice 17,19,20 , and thus likely reflects ≥50% target engagement.…”
Section: Measurement Of Saliva Secretion Ratementioning
confidence: 99%
See 2 more Smart Citations
“…This raises the question of whether PDE4 inhibitor-induced hypothermia may also represent an accurate and thus valuable correlate of the emetic potential of this particular class of drugs. Intriguingly, the potency of PAN-PDE4 inhibitors to induce nausea and/or emesis in humans [ 59 , 76 ], the potency of the same drugs to induce vomiting in animals [ 65 , 80 , 81 ], as well as the potency of these drugs to induce correlates of emesis in animals, such as shortening the duration of α 2 -adrenoceptor-dependent anesthesia [ 52 , 63 , 64 ] and gastric retention [ 54 , 82 ], as well as hypothermia [ 42 ], all align to indicate that first-generation PDE4 inhibitors, such as Rolipram or RS25344, are significantly more emetic than second-generation PDE4 inhibitors. This pattern is confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%